Identification of Cutaneous Leishmaniasis Species in the Dargaz City, Iran - Abdolmajid Fata; Abdolrahim Rezaei; Elham Moghaddas; Faezeh Sadat Mousavi-Vafa; Seyed Aliakbar Shamsian (مجله دانشکده پزشکی اصفهان, 2017)
Background: Cutaneous leishmaniasis is a parasitic skin disease that is endemic in many parts of the world, particularly in Iran. Although the microscopic technique is a common method of diagnosis of leishmaniasis, species of leishmania cannot be differentiated by this method. So, molecular methods have special importance.